(untitled) (Conference on English Language Teaching, 2023)
In order to deliver successful communication, people have to follow cooperative principles which is proposed by Grice. Nevertheless, in a conversation sometimes people fail to follow these cooperative principles which is called non-observant maxim. It consists of violating, flouting, opting out and infringing. This study focuses on investigating the types of flouting maxim and the analysis of why the characters in It Ends with Us novel flout the maxim. The data were collected through document and analyzed by using qualitative descriptive analysis. The result of this study shows that there were 16 utterances flouting of maxim found in the novel. Maxim of relation flouting was the most uttered by the characters and maxim of quality flouting was the least. No flout of maxim of manner found in the novel. The flout of maxims found consist of 5 (33%) flouting maxim of quantity, 3 (20%) flouting the maxim of quality and 7 (47%) flouting maxim of relation.